FEATURES OF COMMUNICATIVE BARRIERS, DIFFICULTIES OF COMMUNICATION AND WAYS TO OVERCOME - Пивхлопко, Диана; Шутяк, Ирина (SWorldJournal, 2021)
The paper deals with the concepts of communication and communication barriers. It describes the essence of the barriers to communication and gives their classification. The main information barriers in the process of communication, the causes of occuranc